Strong association between vertebral endplate defect and Modic change in the general population. Issue 1 (December 2018) - Määttä, Juhani; Rade, Marinko; Freidin, Maxim; Airaksinen, Olavi; Karppinen, Jaro; Williams, Frances
Abstract Modic change (MC) is considered an independent risk factor for low back pain (LBP) but its aetiology remains unclear. In this cross-sectional, large-scale population-based study we sought to characterise associations between endplate defect (ED) and MC in a population sample of broad age range. The study population consisted of 831 twin volunteers (including 4155 discs and 8310 endplates) from TwinsUK. Lumbar T2-weighted MR images were coded for ED and MC. Total endplate (TEP) score was calculated at each intervertebral disc while receiver operating curves (ROC) were calculated to define critical endplate values predictive of MC. MC was detected in 32.1% of the subjects, with a significantly higher prevalence at lower lumbar levels (3.5% at L1/2-L3/4 vs. 15.9% at L4/5-L5/S1, p < 0.001). TEP score was strongly and independently associated with MC at each lumbar level (risk estimates from 1.49 to 2.44; all p ≤ 0.001) after adjustment for age, sex, BMI and twin pairing. ROC analysis showed a TEP score cut-off of 6 above which there was a significantly higher prevalence of MC. In conclusion, ED were strongly associated with MC at every lumbar level. These findings support the hypothesis that endplate defect is a major initiating factor for the cascade of events that may include disc degeneration (DD) and MC.